Does prior 1500-m swimming affect cycling energy expenditure in well-trained triathletes? - Delextrat, A.; Brisswalter, J.; Hausswirth, C.; Bernard, T.; Vallier, J.-M. (Canadian Journal of Applied Physiology, 2005)
The purpose of this study was to determine the effects of a 1,500-m swim on energy expenditure during a subsequent cycle task. Eight well-trained male triathletes (age 26.0 ± 5.0 yrs; height 179.6 ± 4.5 cm; mass 71.3 ± 5.8 kg; VO2max 71.9 ± 7.8 ml·kg-1·min-1) underwent two testing sessions in counterbalanced order. The sessions consisted of a 30-min ride on the cycle ergometer at 75% of maximal aerobic power (MAP), and at a pedaling frequency of 95 rev·min-1, preceded either by a 1,500-m swim at 1.20 m·s-1 (SC trial) or by a cycling warm-up at 30% of MAP (C trial). Respiratory and metabolic data were collected between the 3rd and the 5th min, and between the 28th and 30th min of cycling. The main results indicated a significantly lower gross efficiency (13.0%) and significantly higher blood lactate concentration (56.4%), VO2 (5.0%), HR (9.3%), VE (15.7%), and RF (19.9%) in the SC compared to the C trial after 5 min, p < 0.05. After 30 min, only VE (7.9%) and blood lactate concentration (43.9%) were significantly higher in the SC compared to the C trial, p < 0.05. These results confirm the increase in energy cost previously observed during sprint-distance triathlons and point to the importance of the relative intensity of swimming on energy demand during subsequent cycling.